Influence of seasonal variation on the food safety and shelf-life of homemade dog food from fresh markets in Mueang District, Sakon Nakhon Province - Prachachit, Jakkapat; Bootyothee, Kanokwan; Hemadhulin, Titinan; Pumhirunroj, Benjamabhorn; Sorin, Apisit (Creative Science, 2026)
Home-cooked dog food sold in fresh markets is an alternative for dog owners seeking to avoid commercial dried or canned pet food. Although it is typically boiled and subjected to high heat during preparation, improper storage may lead to spoilage. This study aimed to assess the levels of bacteria, and to determine whether these foods remain microbiologically safe for canine consumption after refrigerated storage, especially when purchased in large quantities, across different seasons and from three fresh market vendors. The study found that all three vendors used leftovers and animal by-products from human consumption, such as the lungs, trachea, bones, blood, and chicken carcasses. During the first day of purchase, the physical characteristics and microbiological quality of the food were acceptable for canine consumption. However, by days 3 and 7 of refrigerated storage, food quality such as smell and texture had declined. Notably, in the rainy and hot seasons, when ambient temperatures were higher, the microbial quality deteriorated significantly, making food unsuitable for dogs. From Day 3 the total microbial counts exceeded the acceptable limit of 1 × 10⁶ CFU g-1 for 2 of 3 vendors (6.05±0.03 and 7.12±0.01) in the summer and all vendors in the rainy season (7.32±0.03, 6.25±0.01 and 7.12±0.01), which posed health risks and might lead to gastrointestinal infections. The pathogenic bacteria which found in this study are Escherichia coli and coliform bacteria. Health risks are not limited to dogs; pet owners who prepare and handle this food directly may also be exposed to potential pathogens. This study recommends that dog owners purchase only a daily portion of this type of food to reduce spoilage risks, particularly given Thailand’s predominantly warm climate. GRAPHICAL ABSTRACT HIGHLIGHTS Homemade dog food in Thailand has gained increasing popularity and is widely available in fresh markets, which typically formulated using by-products from slaughter, such as lungs and blood. Refrigerated storage of dog food may lead to spoilage, which can result in gastrointestinal infections in dogs, moreover may pose a health risk to pet owners who come into contact with the contaminated dog food. Seasonal variations affect the quality of refrigerated dog food. It is not recommended to stockpile home-cook dog food during the rainy or hot seasons, as it should be consumed on the day of purchase to ensure safety and freshness.